Evaluation of through-thickness residual stresses and microstructure in SA516 Gr. 70 steel welds. (May 2021) - Taraphdar, Pradeeptta Kumar; Mahapatra, Manas Mohan; Pradhan, Arun Kumar; Singh, Pavan Kumar; Sharma, Kamal; Kumar, Suranjit
The critical working condition of nuclear power plant equipment necessitates meticulous determination of the welding process and parameters. In this work, some major influential factors of welding were investigated to observe their effects on the through-thickness residual stress distribution in multipass pressure vessel steel welds. In this regard, experiments were conducted to find the characteristics of residual stresses dispersed in SA516 Grade 70 steel welds of different groove geometries with distinct welding conditions. Three-dimensional finite element models of the weldments were developed considering a moving heat source with temperature-dependent material properties to simulate the welding thermal cycles and corresponding residual stress fields. Effects of weld groove geometry, number of weld passes, external constraints, and preheating on the through-thickness residual stress fields were studied. Additional attention was given to the evaluation of the heterogeneous microstructure and microhardness across the weld cross-section associated with their weld thermal history. Finally, the evolution of the through-thickness residual stresses attributed to subsequent weld passes was elaborated.